Model Curriculum for Rotating Resident Physicians in Basic Emergency Medicine - Michael Fitch; Nicholas Kman (Association of American Medical Colleges, 2007)
Abstract This educational resource provides a model curriculum for rotating resident physicians completing a clinical rotation in emergency medicine. This curriculum outline is intended for use by emergency medicine faculty members who are responsible for coordinating, administering, or creating a rotation experience for physicians in training from a wide variety of clinical specialties. These "off-service residents" who may participate in such a curriculum may include first- and second-year residents from the anesthesiology, family practice, obstetrics and gynecology, internal medicine, and surgical specialties. The goal of this curriculum is to provide educational resources, objectives, and guidelines to faculty sponsors of these rotations in order to help enhance the educational experience of participating resident physicians. These materials are not currently widely available for this type of educational rotation experience, and the guidelines and supplemental materials presented here are intended to be freely modified and adapted for use in academic or community medical centers to fit the needs of the organizing faculty members. The materials provided in this curriculum are currently in use at the authors' institution. The template presented here was created and refined over a 2-year period of implementation and reflects meetings, discussions, and interactions with over 150 resident physicians who completed our rotation during that time period.